Ordinary Legal Remedies according to Provisions of Legislation from 1853 and 1860 - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The article sheds light on provisions of Codes of Civil Procedure of 1853 and 1860 concerning ordinary legal remedies. As this matter was codified for the first time, a necessity of amending and supplementing some provisions soon emerged. Those amendments and supplements, along with original provisions were examined in this paper. The author also deals with regulations on jurisdiction of Court of Appeal, Court of Cassation and Supreme court. Types and categories of ordinary legal remedies were scrutinized, as well as strict time limits within one should lodge an appeal and proper grounds for making an appeal. The author also responds to questions under which circumstances are ordinary legal remedies allowed, and what types of decisions a higher court can make after reviewing the correctness and reasonableness of a decision issued by a lower court. Shortly after enactment of the Code of 1853 it appeared that judicial procedure is too complicated, expensive and ineffective due to too many legal remedies and legal jurisdictions. That is the reason why the Supreme court as the highest court within the hierarchy of legal jurisdictions and as final court of appeal was abolished in 1860, when new Code of Civil Procedure had been passed. New codification envisaged Court of Appeal as second instance court and, at the same time, court of last resort. Regarding legal remedies, Code of 1860 introduced appeal as sole  ordinary legal remedy.